2014
DOI: 10.1007/s00167-014-3178-z
|View full text |Cite
|
Sign up to set email alerts
|

Different femorotibial contact points between fixed- and mobile-bearing TKAs do not show clinical impact

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…No difference was observed for KS scores. The mean (SD) FJS-12 score for the fixed bearing was 71 (28) compared to 56.5 (30) for the mobile bearing (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No difference was observed for KS scores. The mean (SD) FJS-12 score for the fixed bearing was 71 (28) compared to 56.5 (30) for the mobile bearing (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors attempted to compare fixed-and mobile-bearing TKA with conventional scores such as the WOMAC, Oxford, KSS, and VA Scores (VAS) and found no difference in clinical outcomes [1,16,20,30]. A jointspecific score that is more responsive such as the FJS-12 is a more discerning measure of patient outcome observing for the first time a difference between these two treatment options [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The femorotibial contact points at 90° of flexion and their relation with anterior knee pain were recently analyzed by van Stralen et al (19) using the study population of the randomized multi-centre trial of Jacobs et al (20). They found that the contact point was significantly more anterior in MB than in FB TKAs (59.5% SD 7.8 vs. 66.1% SD 5.3 of the tibial plateau), with the FB group comparable to the healthy non-prosthetic knees.…”
mentioning
confidence: 99%
“…As the mobile bearing insert is not visible on x‐ray images, mobile bearing translations were estimated from the projected mJSW line. This point is also known as the femoro‐tibial contact point . The mJSW line reflect the center position of the bearing and the projected point on the tibia surface reflect the anterior‐posterior (AP) and medio‐lateral (ML) position of the bearing in respect to the flat tibial surface (Fig.…”
Section: Methodsmentioning
confidence: 99%